Discourse Analysis of Directive Speech Acts Used by Teachers in Classroom Interactions - Aini, Qurrotu; Hidayat, Didin Nuruddin; Husna, Nida; Alek, Alek (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
This study investigates the types of directive speech acts employed by English teachers in online classroom interaction with their students. In addition, the study details the frequency with which teachers in the third grade of SD IT Widya Cendekia use directive speech acts in the context of online learning and classroom interactions. As a descriptive research method, this analysis was designed. The information gleaned from the English class video recording through the Microsoft team application as a learning tool. According to Yule's theory of directive speech act, video recordings were used to capture data for analysis. The study employed Miles and Huberman (1994) qualitative approach to data analysis. According to the findings of this study of teachers' use of directive speech acts in online learning contexts, only 7 of 62 directive utterances were classified as commands, nine as requests, two as suggestions, two as invites, and one as a warning. Besides, the request kind of directive is employed by English teachers in online classroom interactions at a significantly higher frequency than any other form of directive speech acts.